FOREST NURSERY SCHOOL - NEW POSSIBILITIES FOR DEVELOPMENT OF CHILDREN KINDERGARTEN - KVAPIL, Luděk (Trends in education, 2012)
The paper relies on forest pedagogy and deals with the education of children in kindergarten LMS.
Keywords: Forestry forestry education; forest nursery; environmental education; the environment; practical activities.